Specifics of costs classification as a key object of managerial accounting in hotel industry - I. Rogova (Вестник университета, 2017)
The article highlights the problems of managerial accounting in hospitality industry with view of hotel business functioning in terms of tough competition. The key object of managerial accounting is costs estimation. The article views the specifics of costs classification for companies operating in hospitality industry. The emphasis is put on costs classification for calculating net cost of hotel services, which serves as the basis for price setting, profitability estimation and taking key managerial decisions.